Unravelling Magnetic Nanochain Formation in Dispersion for In Vivo Applications. Issue 24 (7th May 2021) - Nandakumaran, Nileena; Barnsley, Lester; Feoktystov, Artem; Ivanov, Sergei A.; Huber, Dale L.; Fruhner, Lisa S.; Leffler, Vanessa; Ehlert, Sascha; Kentzinger, Emmanuel; Qdemat, Asma; Bhatnagar‐Schöffmann, Tanvi; Rücker, Ulrich; et al.
Abstract: Self‐assembly of iron oxide nanoparticles (IONPs) into 1D chains is appealing, because of their biocompatibility and higher mobility compared to 2D/3D assemblies while traversing the circulatory passages and blood vessels for in vivo biomedical applications. In this work, parameters such as size, concentration, composition, and magnetic field, responsible for chain formation of IONPs in a dispersion as opposed to spatially confining substrates, are examined. In particular, the monodisperse 27 nm IONPs synthesized by an extended LaMer mechanism are shown to form chains at 4 mT, which are lengthened with applied field reaching 270 nm at 2.2 T. The chain lengths are completely reversible in field. Using a combination of scattering methods and reverse Monte Carlo simulations the formation of chains is directly visualized. The visualization of real‐space IONPs assemblies formed in dispersions presents a novel tool for biomedical researchers. This allows for rapid exploration of the behavior of IONPs in solution in a broad parameter space and unambiguous extraction of ​the parameters of the equilibrium structures. Additionally, it can be extended to study novel assemblies formed by more complex geometries of IONPs. Abstract : Biocompatible iron oxide nanoparticles in dispersion can be controlled to form flexible and reversible chains in the presence of a magnetic field, which is useful for biomedical applications. The role of control parameters is determined and these novel assemblies formed in dispersions are visualized using advanced scattering methods and reverse Monte Carlo simulations.